Correlation of clinical findings and brain volume data in multiple sclerosis - Fragoso, Yara Dadalti; Wille, Paulo Roberto; Abreu, Marcelo; Brooks, Joseph Bruno B.; Dias, Ronaldo Maciel; Duarte, Juliana Avila; Farage, Luciano; Finkelsztejn, Alessandro; Frohlich, Alan Christmann; Goncalves, Marcus Vinicius Magno; Guedes, Bruno V. Sobreira; Medeiros, Leonardo [UNESP]; et al. (Elsevier, 2017)
Brain volume measurements are becoming an important tool for assessing success in controlling multiple sclerosis (MS) activity. MSmetrix (icometrix) is an easy-to-use platform, specific for MS magnetic resonance imaging (MRI) of the brain. It provides data on total brain volume, grey matter volume and lesion load volume. The objective of the present study was to assess whether disability and the number of relapses during the previous year correlated with brain volume measurements from MSmetrix. Data on 185 icometrix reports from patients with MS were used to evaluate the potential correlation between brain volume measurements and clinical parameters. There was a significant correlation between higher disability and decreased brain volume (total and grey matter). Increased lesion load in the brain and higher number of relapses in the previous year were also independently correlated with decreased brain tissue volume and with increased disability. This is the first study with real-world data to show that icometrix is a relevant tool for the study of brain volume loss in MS.
Keywords: Brain atrophy; Brain volume; Disability; Magnetic resonance image; Multiple sclerosis